Some Estimates of Rough Bilinear Fractional Integral. (20th November 2012) - Fan, Yun; Gao, Guilian
Abstract : We study the boundedness of rough bilinear fractional integral B Ω, α on Morrey spaces L p, λ ( ℝ n ) and modified Morrey spaces L ~ p, λ ( ℝ n ) and obtain some sufficient and necessary conditions on the parameters. Furthermore, we consider the boundedness of B Ω, α on generalized central Morrey space B ˙ p, φ ( ℝ n ) . These extend some known results.